2001
DOI: 10.1002/1522-726x(200102)52:2<208::aid-ccd1049>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Rotational atherectomy (stentablation) in a lesion with stent underexpansion due to heavily calcified plaque

Abstract: We report treatment of a lesion with coronary stent underexpansion due to heavily calcified plaque. Conventional balloon angioplasty was attempted for in-stent restenosis, but the lesion was undilatable despite 25-atm inflation pressure. Intravascular ultrasound (IVUS) revealed stent underexpansion due to heavily calcified plaque. Rotational atherectomy was performed using a stepped burr approach, after which repeat IVUS revealed marked ablation of the stent-calcium complex. Adjunctive balloon angioplasty then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 12 publications
1
44
0
2
Order By: Relevance
“…The excellent resolution of optical coherence tomography permits detailed in vivo 2-dimensional imaging of plaque morphological characteristics (e.g., calcification, lipid, Rotational atherectomy in RCTs was associated with higher rates of MACE at 30 days and no reduction in restenosis. It has a limited role in facilitating the dilation or stenting of lesions that cannot be crossed or expanded with PCI (520,521). Devices for directional coronary atherectomy are no longer marketed in the United States.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…The excellent resolution of optical coherence tomography permits detailed in vivo 2-dimensional imaging of plaque morphological characteristics (e.g., calcification, lipid, Rotational atherectomy in RCTs was associated with higher rates of MACE at 30 days and no reduction in restenosis. It has a limited role in facilitating the dilation or stenting of lesions that cannot be crossed or expanded with PCI (520,521). Devices for directional coronary atherectomy are no longer marketed in the United States.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Among the various adjunct devices that are used to facilitate PCI in severely calcified lesions, only rotational atherectomy has been shown to have potential utility (514,757). Although rotational atherectomy increases the chances of angiographic success in severely calcified lesions, its use as a stand-alone device has not led to a reduction in restenosis (520,521,758). Several retrospective studies have shown that in patients with severely calcified lesions, the use of rotational atherectomy before implantation of BMS (514) or DES (515) is safe.…”
Section: (Level Of Evidence: C)mentioning
confidence: 99%
“…Stentablation by RA has been reported since 2001 as an option to resolve unexpanded stents. 7) There are concerns regarding excessive stent damage, distal embolization of metal particles, excessive heat generation, and burr entrapment in the stent; 8,9) based on this, all authors have agreed that stentablation is the last choice to manage an underexpanded stent. Khan, et al 10) reported emergency surgical extraction of an entrapped burr within the stent at a mid-LAD artery lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Métodos adjuntos de ablação, como aterectomia rotacional e laser, têm sido empregados nesses casos para modificar a complacência do vaso, garantindo a expansão adequada do stent [5][6][7] .…”
Section: Discussionunclassified
“…A aterectomia rotacional foi realizada no segmento reestenótico, , com velocidade ajustada para 150.000 rpm, utilizando-se diâmetros da ogiva progressivamente maiores até 2,25 mm e períodos de ablação inferiores a 30 segundos, tomando-se o cui- O mecanismo de atuação da aterectomia rotacional, quando realizada dentro de stent hipoexpandido, está relacionado tanto à ablação das hastes do stent e do tecido justaposto ao mesmo, como à modificação da placa calcificada subjacente. As vibrações geradas pela ogiva podem ser transmitidas através das hastes do stent para a parede vascular, gerando microfraturas, que podem facilitar a fratura posterior do tecido calcificado com cateter-balão a alta pressão 7 . Em nosso caso, a aterectomia rotacional com técnica apropriada e a posterior insuflação com balão permitiram expansão da prótese e ganho luminal adequados.…”
Section: Discussionunclassified